2009
DOI: 10.1111/j.1600-0463.2009.02509.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence genes of Clostridium difficile by multiplex PCR

Abstract: Clostridium difficile strains belonging to the PCR ribotype 027, pulse-field gel electrophoresis (PFGE) type NAP1, toxinotype III and restriction endonuclease analysis group BI harbouring mutations in the tcdC gene and possessing binary toxin components A and B have been described to cause epidemics with increased morbidity and mortality. In the present study we developed a conventional multiplex PCR designed to detect selected virulence associated markers of the hypervirulent C. difficile PCR ribotype 027. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…This may well explain why several studies have reported that an aberrant tcdC genotype does not predict increased toxin production or, indeed, increased virulence (4,6,26,32,39). Notwithstanding this, it should be emphasized that the ⌬117 tcdC frameshift mutation still provides a convenient basis upon which to make a presumptive identification of PCR ribotype 027 strains (1,3,9,40), even though this itself does not provide a broadly applicable rationale for the perceived notion that PCR ribotype 027 strains are "high-level" toxin producers.…”
Section: Discussionmentioning
confidence: 99%
“…This may well explain why several studies have reported that an aberrant tcdC genotype does not predict increased toxin production or, indeed, increased virulence (4,6,26,32,39). Notwithstanding this, it should be emphasized that the ⌬117 tcdC frameshift mutation still provides a convenient basis upon which to make a presumptive identification of PCR ribotype 027 strains (1,3,9,40), even though this itself does not provide a broadly applicable rationale for the perceived notion that PCR ribotype 027 strains are "high-level" toxin producers.…”
Section: Discussionmentioning
confidence: 99%
“…Lem ee et al (2004) [140] designed a multiplex PCR for the simultaneous identification and toxigenic type characterisation of C. difficile isolates. Several other studies have proposed different multiplex PCR primers and protocols not only to detect the genes encoding the major toxins A and B but also to detect binary toxin genes (cdtA and cdtB) and other deletions in the Paloc genes [174].…”
Section: Difficile Typing Methodsmentioning
confidence: 99%
“…All unique strains were compared with the Cardiff-European Center for Disease Control (ECDC) collection of C. difficile strains; a Washington University (WU) strain number was assigned to unique strains that did not match any in the Cardiff-ECDC collection. All C. difficile isolates were also tested by PCR for the presence of tcdA and tcdB and binary toxin genes by PCR, as previously described (23,31).…”
Section: Methodsmentioning
confidence: 99%